An Assessment of the Contributions of Muslim Women Organizations in Promoting Spiritual Growth and Health Care Delivery in Gombe State - Lubabatu Mohammad Magaji; Akilu Aliyu Muhammad; Jibrin Mohammed (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2026)
Aim: This study assesses the contributions of Muslim women’s organizations to promoting spiritual growth and healthcare delivery in Gombe State, Nigeria. Specifically, it examines the roles, strategies, and outcomes of the Federation of Muslim Women’s Associations in Nigeria (FOMWAN), the Islamic Medical Association of Nigeria (IMAN) Sisters Wing, and the Naseehah Foundation in addressing the interconnected spiritual, health, and social needs of women and their communities. Methodology: The study adopts a qualitative research design incorporating historical, descriptive, and empirical approaches. Data were collected through oral interviews, participant observation, and documentary sources. The data were analyzed thematically to examine the organizations’ activities, strategies, contributions, and challenges in promoting Islamic spiritual development and improving access to healthcare services across Gombe State. Results: The findings reveal that the three organizations make significant and complementary contributions to spiritual development, healthcare delivery, and community welfare. FOMWAN contributes through Islamic education, health-awareness programmes, healthcare facilities, and community initiatives. The IMAN Sisters Wing provides medical services and promotes healthcare practices informed by Islamic medical ethics. The Naseehah Foundation focuses particularly on spiritual guidance, counselling, moral admonition, and interventions aimed at addressing behaviours perceived as socially and morally harmful. Collectively, these activities demonstrate the capacity of Muslim women’s organizations to combine religious education, health promotion, medical outreach, counselling, and community development. However, their effectiveness is constrained by inadequate funding, insufficient staffing, and limited facilities. Conclusion/Novelty: The study concludes that Muslim women’s organizations constitute important community-based actors in advancing both spiritual well-being and healthcare delivery in Gombe State. Their integrated approach demonstrates that religious and health interventions can operate complementarily in addressing community needs. The novelty of the study lies in providing a focused comparative assessment of three Muslim women-led organizations and highlighting their interconnected contributions to spiritual development and healthcare provision within the state. The study recommends institutional formalization, capacity building, sustainable income-generating strategies, and stronger collaboration with government agencies and relevant stakeholders to enhance the scale, sustainability, and effectiveness of their interventions.